Captain Matias Porras in the guerilla movement in Pototan (1942-1945). - Elumba, Madonna E.
This study documents the role of Captain Matias Porras in the guerilla movement in Pototan during the Japanese occupation of Panay from 1942 to 1945. It aims to achieve the following objectives: 1) to find out and discuss the conditions that led to the Japanese encroachment into the Philippines; 2) to document the conditions of Pototan prior to the coming of the Japanese and during their occupation; 3) to trace the origin and characterize the development of the guerilla movement in Pototan and identify its linkages with the larger guerilla movement in Panay; 4) to document and discuss the role of Captain Matias Porras in the movement and discuss the reasons and factors that led to the success of the guerilla movement; and 5) to establish the significance of the local resistance movement in relation to Panay's struggle for liberation from the Japanese. , The researchers did library research from various collections in Iloilo, including archival materials in some government agencies. They also relied on extensive interviews with key informants -- Captain Matias Porras' daugthers, relatives, friends, acquaintances, soldiers, and people who have knowledge of the conditions of Pototan prior to and during its occupation by Japanese and the guerilla movement under the leadership of Porras. The researchers' interest in the guerilla movement in the Panay Island is based on the fact that General Douglas MacArthur did not appear to have any specific plans for defending the Visayan Islands. Almost all of the regiments in the Visayas were ordered to transfer to Luzon to aid the USAFFE forces there. The town of Pototan is centrally and strategically located astride Panay Island's railroad and road systems that link several interior towns. Futher resistance movement in Pototan was one which was initiated by a local figure, Matias Porras, and only later linked with the broader movement elsewhere throughout the archipelago. Captain Porras played a significant role in the guerilla movement in Pototan as its founder and leader. With his men, he was vital in protecting and defending many people, especially Pototanons. Without him, many could have been tortured and killed by the Japanese forces and other guerillas.